Relation between bruxism and dental implants - Torcato, Leonardo Bueno [UNESP]; Brandini, Daniela Atili [UNESP]; Falcón-Antenucci, Rosse Mary [UNESP]; Zuim, Paulo Renato Junqueira [UNESP] (My University, 2014)
OBJECTIVE: The aim of this study was to gather information and discuss the predictability of implant-supported prostheses in patients with bruxism by performing a literature review. METHODS: In order to select the studies included in this review, a detailed search was performed in PubMed and Medline databases, using the following key words: bruxism, dental implants, implant supported prosthesis, and dental restoration failure. Items that were included are: case reports, randomized controlled trials, in vitro studies, literature and systematic reviews, with or without meta-analysis, of the last 20 years that addressed the theme. Articles without abstracts, animal studies, articles in languages other than English and articles from journals unrelated to the dental field were excluded. RESULTS: after analysis according to inclusion and exclusion criteria, 28 articles were selected from a total of 54. It is known from the array of scientific articles which have assessed, either through retrospective, prospective or experimental studies, that the biomechanical and biological impact of bruxism on implant-supported prostheses is small, and that the literature has contributed little to exemplify the prosthetic limits of safety for the specialist from a clinical point of view. CONCLUSION: Although there is still no general consensus on this matter, most of the literature review articles do provide clinical guidelines that contribute to implant supported prostheses longevity and stability in patients with bruxism.

OBJETIVO: Realizar uma revisão sistemática, a fim de reunir informações e discutir a previsibilidade de próteses sobre implantes em pacientes com bruxismo. MÉTODOS: Para a identificação dos estudos dessa revisão, foi realizada uma estratégia de busca detalhada e avançada nos bancos de dados PubMed e Medline. Foram utilizados como descritores: bruxismo, implantes dentários, prótese implantossuportada e falha da restauração dentárial; bruxism, dental implants, implant-supported prosthesis e dental restoration failure. Os critérios de inclusão foram: artigos clínicos, estudos controlados aleatórios, estudos in vitro, revisões de literatura e revisões sistemáticas com e sem meta-análise dos últimos 20 anos que abordassem o tema proposto. Os critérios de exclusão foram: artigos sem resumo, estudos em animais, artigos cujo idioma não fosse o inglês e artigos de periódicos que não pertencessem à área odontológica. RESULTADOS: De um total de 54 artigos, após uma análise segundo o critério de inclusão e exclusão, foram selecionados 28 artigos. É sabido que a quantidade de artigos científicos que avaliaram, seja através de estudos retrospectivos, prospectivos ou experimentais, o impacto biológico e biomecânico do bruxismo em próteses sobre implantes é pequena e pouco tem contribuído para melhor exemplificação e discernimento dos limites protéticos de segurança para o especialista sob um ponto de vista clínico. CONCLUSÃO: Portanto, ainda não há um consenso geral acerca desse assunto, porém, a maioria dos artigos de revisão de literatura fornecem guias de orientação clínica, os quais auxiliam na longevidade e estabilidade de próteses sobre implantes em pacientes com bruxismo.
Relação entre bruxismo e próteses sobre implantes
Keywords: Bruxism; Dental implantation; Dental prosthesis; Bruxismo; Implantação dentária; Prótese dentária